Perceptual distortion of face deletion by local anaesthesia of the human lips and teeth - Türker, Kemal S.; Yeo, Purdee L. M.; Gandevia, Simon C. (Experimental brain research, 2005)
As visual guidance of facial movements is impossible, accurate movements for speech and mastication require an established body image that is formed via the information from mechanoreceptors in the skin, mucosa, periodontium, and proprioceptors in the facial and masticatory muscles and in the jaw joints. In this study we aimed to investigate how the acute deafferentation of lips and teeth alters the established image of lips, teeth and the thumb. We used a psychophysical method to determine whether the perceived sizes of the upper lip and front teeth change when the sensory input from the lips and front teeth is fully blocked. We also examined the perceived size of the thumb to test for acute interactions between the thumb and facial structures. Local anaesthetic blocking of upper lip and upper front teeth significantly increased the perceived size of the upper lip by as much as 100% (range 21-100%) in ten out of eleven subjects tested (overall mean 52%; p=0.001). The perceived size of the upper teeth also significantly increased by as much as 155% (range 30-155%) in eight of the eleven subjects during anaesthesia (overall mean 41%; p=0.035). When the region of anaesthesia was increased and both upper and lower teeth and lips were anaesthetised, the perceived size of the upper lip again increased, by 53% (p=0.040), but the change in perceived size of the upper front teeth (18%) was not significant (p=0.206). In both studies there was no change in perceived size of the thumb. The results illustrate the labile central interaction between sensory inputs and the importance of feedback from peripheral afferents in generating the subjective facial image. The timing, level, and area of anaesthesia may be important modifiers of these interactions.